Iceland (Makerspaces in the Early Years) - Dr Sólveig Jakobsdóttir; Dr Margrét E. Ólafsdóttir; Þórdís Sævarsdóttir; Dr Svanborg R. Jónsdóttir; Kristín Dýrfjörð; Skúlína H. Kjartansdóttir; Dr Torfi Hjartarson; Anna Elisa Hreiðarsdóttir; Svava Pétursdóttir (2019)
There were four projects undertaken in Iceland. The first was an observation of makerspaces run by Innoent which involved children from mixed ages, from 5-10, but the focus for the observations was the children under eight. The second was a pre-school involving nine children aged 5 and 6, in which children’s coding activities were observed. The third case study took place in a school and involved observations of ten children aged 7 who were involved in a Minecraft club. The final project involved interviews with 8 teachers of 17 children aged 6-8, who developed makerspaces in their schools. Anonymised field notes and transcribed interviews are available in the repository.